SELISIH HARGA PADA BANDROL PRODUK DALAM PERSPEKTIF MUAMALAH - R. Hozin Abdul Fatah; Muhammad Saleh (Mutawasith: Jurnal Hukum Islam, 2018)
This research aims to find out the law of sale and purchase in Indomaret regarding the difference in the price of product A. The method used is field research. This type of qualitative approach is to emphasize the inductive analysis of thought processes relating to the dynamic of the relationship between observed phenomena and the use of scientific logic. Methods of collecting interviews and documentation data. The conclusion of this research is the buying and selling transaction in Indomaret Suryalaya law including buy and sell Fashid and found a gharar element in it is in the contract, but the Gharar element found in Indomaret Suryalaya is not Making this buy and sell is forbidden, because the gharar element that is in this buy and sell light include Gharar which is allowed the most important in buying and selling between the two parties like the same like, mutual and no compulsion.